Statistical analysis of the output power of a hybrid wind-solar-tidal energy source - Liu, Jie. (2010)
With rapid development of the economy in many parts of the world, increasing amount of energy is required. In most cases, large amounts of fossil fuels are consumed to generate electricity. However, fossil fuels produce pollutions and can damage greatly the environment. Due to their clean, renewable and environmental-friendly characteristics, so renewable energy sources are being actively pursued. Although renewable energy sources have many advantages, they are closely related to the weather, climate and season. Hence the sources are random and uncontrollable. When the generated electricity does not match the load demand, there will be deviations in the network voltage and frequency which can lead to unacceptable power quality. So the purpose of this project is to study a scheme to control the output power from the random renewable sources so that acceptable power quality can be achieved. Specifically, a power generation scheme which includes a battery energy storage system has been considered. The output (dispatch) power level from the renewable-battery energy storage system is a constant value determined from the average value of the renewable generated power. The discharge energy from, and the charged energy into the battery energy storage system will be the same over a specified interval. When the generated power is below the constant dispatch power level, the battery will discharge to maintain the dispatch power constant. Conversely, if the generated power is above the rated power, the battery will be charged to keep the dispatch power to the specified level.